Expressão imuno-histoquímica das proteínas IFN-ƴ e TGF-β1 em cistos radiculares e cistos dentígeros - Rocha Neto, Pedro Carlos da (2012)
Odontogenic cysts are pathologic cavities covered by odontogenic epithelium and filled by liquid, desquamated cells or other materials. The intraosseous lesions, such as radicular cyst and dentigerous cyst, present a potential of expansion capable of promoting the destruction of the surrounding osseous tissue. The mechanisms related to this process of expansion are the proliferation of cystic epithelium, the increase of the osmolarity of the cystic fluid and the synthesis of reabsorption factors such as IFN-γ and TGF-β1. The aim of this study was to evaluate and compare the immunohistochemical expression of IFN-γ and TGF-β1 between radicular cysts and dentigerous cysts in order to understand the role and behavior of these proteins in the expansion of these cysts. We selected 20 cases of radicular cyst and 20 cases of dentigerous cyst chosen from the files of UFRN s Laboratory of Oral Pathology. After analyzing the clinical data, the cases underwent the routine staining technique (HE) and immunohistochemistry for the appearance of IFN-γ and TGF-β1 in the epithelium and capsule of these cysts. The statistical analysis using the Mann-Whitney test revealed no statistically significant difference in immunoexpression of IFN-γ between the epithelium (p = 0.565) and capsules (p = 0.414) of radicular cysts and dentigerous cysts. Moreover, there was no statistically significant difference of immunoexpression of TGF-β1 between the epithelium (p = 0.620) and capsules (p = 0.056) of radicular cysts and dentigerous cysts. The Wilcoxon test revealed no statistically significant difference between IFN-γ and TGF-β1 imunoexpressions in the epithelium (p = 0.225) and capsules (p = 0.370) of radicular cysts. There was no statistically significant difference between IFN-γ and TGF-β1 imunoexpressions in the epithelium (p = 0.361) of dentigerous cysts. However, there was a statistically significant difference between IFN-γ and TGF-β1 immunoexpressions in the capsule (p = 0.001) of dentigerous cysts, being TGF-β1 the factor which presented the most significant immunoexpression. Given these results, we conclude that there was no difference in immunohistochemical expression of IFN-γ and TGF-β1 between radicular and dentigerous cysts and that TGF-β1 was more significant than the IFN-γ in the capsule of dentigerous cysts